A rare EGFR mutation L747P conferred therapeutic efficacy to both geﬁtinib and osimertinib: A case report. (December 2020) - Huang, Xiaojie; Yang, Yan; Wang, Pingli; Wang, Jia; Chen, Songan; Mao, Xinru; Ding, Liren
Highlights: Both first- and third-generation EGFR-TKIs showed therapeutic efficacy with EGFR L747 P. This is the first clinical evidence describing the clinical efficacy of osimertinib for EGFR L747 P. Abstract: EGFR mutations, primarily sensitizing mutations such as exon 19 deletion and exon 21 point mutations, have been proven to act as predictive biomarkers for the response to tyrosine kinase inhibitors (TKIs). How patients harboring EGFR L747 P (a rare mutation located in exon 19) respond to EGFR-TKI is controversial. Some studies have described EGFR L747 P as providing intrinsic resistance to EGFR-TKIs, but others support this rare mutation as a sensitive mutation. Hence, we reported a patient with advanced lung adenocarcinoma harboring an EGFR L747 P who benefited from first-line treatment with gefitinib. This patient achieved stable disease (SD) and had a progression-free survival (PFS) of 18 months. After disease progression, this patient was subsequently administered osimertinib and responded, as evidenced by a significant reduction in nodular lesions. This case revealed that EGFR L747 P rendered both geﬁtinib and osimertinib therapeutically efficacious.